"So, Are We Good?" the Emerging Sensitive New Man Movement in the Boys' Club of Stand-up Comedy - (:unkn) unknown (My University, 2014)
This thesis discusses the emerging new man comedic persona in contemporary stand-up comedy. The new man comedian eschews the hypermasculine and heteronormative traits that were common among male stand-up comedians during the boom era (1980s-1990s). The new trend of a feminized and feminist comedic persona will be analyzed through case studies of two comedians: Louis C.K. and Marc Maron. Their comedic personae transcend their on-stage comedic routines and are augmented through transmedia texts. In the case of Louis C.K., he challenges the audience's perception of his persona through his semi-autobiographical and sometimes surrealistic television series, Louie. Maron's comedic persona is amplified through his podcast, WTF, as well as his appearances in other media where he is portraying a version of himself. Each comedian's relationship with their audience and their contemporaries will be discussed, both in fictional and non-fictional texts. The emergence of new man comedy through these two comedians also leads to a new theory of stand-up comedy as media genre: That the end goal of stand-up comedy is more than just making the audience laugh.
Keywords: Gender Dichotomy; Louis C.k.; Marc Maron; Masculinity; Podcast; Stand-up Comedy